Disinformation: Slow Burn Menace - Jayakumar, Shashi (2017)
Should state-sponsored disinformation campaigns be ranked as a national security threat on par with terror or cyber threats? How can the Singapore polity secure itself against such threats, and who should do what in the effort to shore up national resilience against this threat?